Dynamic shifts in chromatin states differentially mark the proliferative basal cells and terminally differentiated cells of the developing epidermis - Yan Ting Shue; Kang Ting Lee; Benjamin William Walters; Hui Binn Ong; Shaktheeshwari Silvaraju; Wei Jun Lam; Chin Yan Lim (Epigenetics, 2020)
Post-translational modifications on nucleosomal histones represent a key epigenetic regulatory mechanism to mediate the complex gene expression, DNA replication, and cell cycle changes that occur in embryonic cells undergoing lineage specification, maturation, and differentiation during development. Here, we investigated the dynamics of 13 key histone marks in epidermal cells at three distinct stages of embryonic skin development and identified significant changes that corresponded with the maturation of the proliferative basal epidermal cells and terminally differentiated cells in the stratified layers. In particular, H3K4me3 and H3K27ac were accumulated and became more prominent in the basal cells at later stages of epidermal development, while H3K27me3 was found to be low in the basal cells but highly enriched in the differentiated suprabasal cell types. Constitutive heterochromatin marked by H4K20me3 was also significantly elevated in differentiated epidermal cells at late gestation stages, which exhibited a concomitant loss of H4K16 acetylation. These differential chromatin profiles were established in the embryonic skin by gestation day 15 and further amplified at E18 and in postnatal skin. Our results reveal the dynamic chromatin states that occur as epidermal progenitor cells commit to the lineage and differentiate into the different cells of the stratified epidermis and provide insight to the underlying epigenetic pathways that support normal epidermal development and homoeostasis.